Stress Intensity Factors of Tubular T/Y-Joints Subjected to Three Basic Loading - Lie, Seng Tjhen (2016)
This paper describes the determination of stress intensity factors (SIFs) of a 3D surface crack in acircular hollow section (CHS) T/Y-joint subjected to three basic loading. In order to achieve the main objective, anautomatic finite element (FE) mesh generator is designed whereby the mesh density and element type of the CrackTube zone can be controlled by the users. Extensive tests are carried out to check the accuracy and to test theconvergence of the mesh models. It is found that the generated mesh models are both accurate and robust.Subsequently, a total of 246 cracked CHS T/Y-joints subjected to axial loading; in-plane bending and out-of-planebending are analysed, and the influencing parameters β, γ, τ, θ, a/t0 and c/a on the SIFs of a 3D surface crack areinvestigated in this study. The SIFs at the deepest point of a 3D surface crack are also determined using an indirectmethod incorporated in BS7910. It is found that the later underestimates the SIFs by as much as -36.9% under axialload for crack located at the crown and -32.9% under out-of-plane bending for crack located at the saddle,respectively. Hence, the indirect method is found to be unsafe in estimating the SIFs of a 3D surface crack in CHST/Y-joints under certain loading conditions and crack location.